Narrative Mourning : Death and Its Relics in the Eighteenth-Century British Novel - Oliver, Kathleen M. (Book collections on Project MUSE., 2020)
Narrative Mourning explores death and its relics as they appear within the confines of the eighteenth-century British novel. It argues that the cultural disappearance of the dead/dying body and the introduction of consciousness as humanity's newfound soul found expression in fictional representations of the relic (object) or relict (person). In the six novels examined in this monograph--Samuel Richardson's Clarissa and Sir Charles Grandison; Sarah Fielding's David Simple and Volume the Last; Henry Mackenzie's The Man of Feeling; and Ann Radcliffe's The Mysteries of Udolpho--the appearance of the relic/relict signals narrative mourning and expresses (often obliquely) changing cultural attitudes toward the dead. Published by Bucknell University Press. Distributed worldwide by Rutgers University Press.